Investigating Interaction Dynamics among Nonoil Economic Growth and Its Most Important Determinants: Evidence from Saudi Arabia - Badr Saleh Al-Abdi; Abdallah M. M. Badr; Faisal A. M. Ali; Tawfik M. A. Jabbar; Fahmy Al–Salwi (Discrete Dynamics in Nature and Society)
Over the past decades, Saudi Arabia’s economic development has strongly depended on oil revenues fueled by the rise of oil prices and the strong global market demands for crude oils. However, the country can no longer depend on oil revenues in the face of the dynamic global market, and hence, the Saudi government’s Vision 2030 seeks to reduce this dependence and diversify the economy’s sources of income. Motivated by this, this study aims to investigate the impact of growth factors: financial innovation (FI), nonoil trade openness (TO), nonoil gross capital formation (GCF), and human capital (CH) development on the nonoil economic growth in Saudi Arabia. The goal of this investigation is to examine the dynamic symmetrical and nonsymmetrical impact of these growth factors on nonoil economic growth and policymaking in Saudi Arabia. To achieve this, this study utilizes the distributed lag symmetric and asymmetric (ARDL and NARD) approaches to assess the short- and long-term symmetric relationships among these growth variables with nonoil economic growth as well as the stationarity, cointegration, and directionality among variables with the theory of “ceteris paribus” in the error correction model (ECM), and Granger causality framework to analyze time-series data from 1980 to 2020. The findings of this study revealed that the FI, TO, GCF, and CH have an impact on the nonoil economic growth in the short and long terms. Additionally, in the long term, the NARDL technique showed that the positive adjustments of HC, FI, TO, and GCF boost the development, which have very significant effects on the nonoil GDP. They also indicate that negative movements have more influence than positive movements in FI. Meanwhile, mixed directional causation results were observed in the short-run analyses. Overall, the findings of this study provide significant insights, empirical recommendations, and implications for policymakers striving to achieve sustainable nonoil trade economic growth in Saudi Arabia and the region.